REVOLUTIONIZING EDUCATION THROUGH FLIPPED LEARNING: TRANSFORMING LEARNING PATTERNS IN THE 21ST CENTURY - Dhea Arti; Aldy Danuar; Tri Pujiani (Wiralodra English Journal, 2025)
This study investigates flipped learning as an emerging instructional approach that addresses the shifting learning needs of learning in the 21st century. Compared to traditional classroom pedagogy with respect to teacher-centered approach, flipped learning transforms traditional direct instruction outside the classroom online and focuses classroom time for group activities, discussions, and experiential learning. The article integrates new empirical and theoretical studies to analyze how the flipped approach results in greater autonomy, critical thinking, and motivation among students. Grounded on constructivist theory, Bloom's Taxonomy, and self-determination theory, this paper examines how flipped classrooms enhance active learning and learner-centered learning. The research concludes that flipped learning results in better academic performance if educators prepare themselves appropriately and digital technologies are made available. However, unequal digital access and learner readiness are issues that still need to be main concerns. EFL case studies also demonstrate that, in addition to promoting language acquisition, flipped learning can promote 21st-century skill acquisition such as problem-solving and collaboration. Ultimately, flipped learning presents a convincing way of redesigning education today into an even more engaging, equalitarian, and forward-looking environment.